Agronomic and silage quality traits of winter cereals - Siefers, M.K.; Huck, G.L.; Turner, J.E.; Pendergraft, J.S.; Bolsen, K.K.; Young, Matthew A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Agronomic and silage quality traits were examined for 12 winter cereals harvested at two stages of maturity. Forage dry matter (DM) yields were higher at the mid-dough than the early-heading stage. Post 90 barley had the highest whole-plant DM yield at the early-heading stage, and Presto triticale had the highest yield at the mid-dough stage. Newton wheat had the lowest whole-plant DM yield at both stages of maturity. The first cutting of all varieties originally was intended to be at the late-boot stage, but harvest was delayed by frequent rainfall and wet soils in May, and field-wilting conditions were less than ideal. The range in heads emerge d was 23 to 87%, and the range in the silage DM content at early-heading stage was 19.2 to 46.4%. Both crude protein (CP) and ash contents were higher for the early-heading cereals than the mid-dough. All 24 silages were of relatively low forage quality, as evidenced by high neutral detergent fiber (NDF) and acid detergent fiber (ADF) percentages. Only five silages, the early-heading stage Tomahawk wheat; mid-dough stage Presto triticale; and the mid-dough stage Kanby, Post, and Post 90 barleys, had less than 60% NDF and 40% ADF. Extensive lodging occurred in virtually all cereals before the mid-dough stage harvest.
Keywords: Beef; Winter cereals; Silage; Winter cereal variety; Winter cereal maturity; Winter cereal yield